Inhibition of FOSL2 aggravates the apoptosis of ovarian cancer cells by promoting the formation of inflammasomes - Li, Jie; Zhou, Li; Jiang, Hongye; Lin, Lin; Li, Yinguang (Genes & genomics, 2022)
Background Ovarian cancer is a common gynecological malignancy among female patients and poses a serious threat to women’s health. Although it has been established that Fos-like antigen 2 (FOSL2) is linked to ovarian cancer (OC), its exact role in the development of OC remains unknown. Objective This article aims to investigate the role of FOSL2 in ovarian cancer development. Methods FOSL2 expression in ovarian carcinoma and adjacent tissues was assessed using real-time fluorescent quantitative PCR and western blot. We constructed OE/sh-FOSL2 plasmids and Caspase-1 specific inhibitors (Yvad-CMK) and transfected A 2780 cells with them to identify the relevant cell functions. Furthermore, we used western blot assay to determine the changes in expression of apoptosis-associated speck-like protein containing a CARD (ASC), cysteine aspartate-specific proteasezymogen procaspase 1 (pro-caspase-1), cysteinyl aspartate-specific proteinase-1 (caspase-1), interleukin-1β precursor (pro-IL-1β), interleukin-1β (IL-1β), interleukin-18 precursor (pro-IL-18), and interleukin-18 (IL-18). In addition, we measured the concentration of IL-1β and IL-18 using an enzyme-linked immunosorbent assay (ELISA). Moreover, Tthe level of lactate dehydrogenase (LDH) in the cell supernatant was measured by LDH release assay kit. Results The expression of FOSL2 was significantly higher compared with the surrounding tissues. The proliferation, migration, and invasion of A2780 cells were enhanced after transfection with OE-FOSL2 plasmids; however, the cell apoptosis was significantly decreased. When FOSL2 was overexpressed, the inflammasome-associated proteins such as ASC, caspase-1, IL-1β, and IL-18 were downregulated. Furthermore, FOSL2 induced apoptosis and activated the production of inflammasomes in A2780 cells. Co-therapy with Yvad-CMK and substantially inhibited apoptosis and activation of inflammasomes. Conclusions Inhibition of FOSL2 promotes the apoptosis of OC cells by mediating the formation of an inflammasome.